Professional title promotion among clinicians: a cross-sectional survey. (October 2016) - Liu, Yunfang; Yang, Zhiping; Fan, Daiming
Abstract: Background: Research achievement is essential for promotion in most Chinese medical institutions, causing enormous pressure among clinicians. We believe ours is the first nationwide questionnaire survey about clinicians' attitude to the current title promotion system. The aim of this study is to investigate the present title promotion mechanism and put forward policy recommendations. Methods: We surveyed doctors from regions with different economic development, from a variety of geographical locations, with different degrees of professional title, and working at different levels of hospital in 31 districts in China. Clinicians completed a 29-item survey which included questions about demographic characteristics, work conditions, promotion conditions, the existing promotion system, and suggestions for reform. We used descriptive analysis to compile our findings. The Chinese Academy of Engineering Ethics Committee reviewed the protocol and exempted it from additional ethical approval. Findings: 7020 questionnaires were sent out and 6953 were analysed. 85·8% (5965/6953) of respondents are under great pressure, primarily from desire for promotion (4915 [70·7%]). Much less pressure was reported from doctor–patient tensions (4638/6953 [66·7%]) or work demands (4460 [64·1%]). 67·3% (4678/6953) of respondents reported research achievement was decisive for promotion, while working performance was reported as decisive by 38·8% (2699). 92·2% (6414/6953) reported a belief that the current system for promotion is problematic and 83·7% (5823) that the most important problem is excessive emphasis on research accomplishment. 88·5% (6150/6953) reported that working performance is unduly ignored for promotion. 77·6% (5394/6953) reported having seen people resort to improper means to achieve promotion, and 43·8% (3044) would consider using illicit means themselves. 79·3% (5516/6953) suggested the characteristics of each class of hospital be accommodated in any reform, and 72·9% (5071) suggested that title appraisal should be associated with clinical performance. Interpretation: Doctors should be encouraged to pursue research. However, the current appraisal system with a focus on scientific publication and low emphasis on clinical practice has put burdens onto clinicians and our results suggest this system could lead to academic misconduct. A new appraisal system that takes into account working performance, professional skills, and innovation capacity should be established. For doctors working in community and rural areas, the new system should take limited account of innovation capacity. The survey was limited by the huge number and variety of classifications of clinicians. Funding: Chinese Academy of Engineering (2014-ZD-09)